The Marriage Model in the Gayo Community and Its Impact on the Inheritance System - Hasballah, Khairuddin; Achyar, Gamal (Media Syari'ah, 2024)
The issue of inheritance is closely related to kinship ties, both blood and marital. An example of marriage model in the Gayo community differs from other Acehnese communities, thus leading to different inheritance practices. The Gayo community recognizes three marriage models: jeulen, angkap, and kuso-kini. This is interesting to study in relation to the inheritance system in the Gayo community and its connection to these marriage models. Research findings indicate that inheritance practices in some parts of the Gayo community are greatly influenced by their marriage models. For instance, female children who marry jeulen may not receive inheritance rights, while male children who marry angkap may also be excluded from inheritance. According to traditional Gayo leaders, the inheritance system in the Gayo community is not directly influenced by their marriage system, as they adhere to Islamic inheritance laws. Any deviation from Islamic inheritance laws is attributed to the ignorance of village authorities or the heirs themselves, rather than customary practices. The research also found other inheritance issues practiced by the Gayo community, such as equal distribution of inheritance based on responsibilities towards parents and family. The study also revealed various cultural practices in the Gayo community that warrant further serious and in-depth research, both in terms of marital customs and inheritance systems (such as cases where parents are not given inheritance rights when the heir is still alive), and other related matters.